Why Younger Catholics Seem More Committed: Survivorship Bias and/or "Creative Minority" Effects among British Catholics. Issue 2 (28th April 2022) - Clements, Ben; Bullivant, Stephen
Abstract: The normative value of, and the extent of popular engagement with, different forms of commitment differ across Christian religious traditions, but studies often show women and older people exhibiting greater religiosity in their behavior and belief. Using a multidimensional approach to religious commitment, this study uses a new survey to provide an in‐depth assessment of Catholics in Britain. It finds that younger cohorts show greater involvement in some aspects of commitment and that there is very limited evidence for gender differences. Family religious socialization plays a key role in patterns of commitment relative to the weak impact of schooling. Two potential explanations for this counterintuitively positive "youth effect" seen among British Catholics are offered: "survivor bias" and a "creative minority" effect. The study provides an important contribution to understanding how Catholics in Britain engage with their faith and mediate processes of secularization.